Gnathostoma spinigerum: Molecular cloning, expression and characterization of the cyclophilin protein - Laummaunwai P. (2014)
In this study, a cDNA encoding cyclophilin (CyP) of Gnathostoma spinigerum was cloned into a prokaryotic expression vector and expressed in Escherichia coli. The predicted molecular mass of the putative protein was 18.6. kDa, and the deduced amino acid sequence had 86, 84.8, 81.3 and 77.2% identity with the CyP of Dirofilaria immitis, Brugia malayi, Onchocerca volvulus and Caenorhabditis elegans, respectively. A prediction of linear B-cell epitopes with high hydrophilicity and immunoblotting results indicated that the recombinant CyP has antigenicity to humans. The recombinant CyP protein reacted with human gnathostomiasis sera but not with other parasitosis or healthy control sera, suggesting that it might be useful for the serodiagnosis of human gnathostomiasis. © Elsevier Inc.